Journalism and austerity : digitization and crisis during the Greek Memoranda - Kostopoulos, Christos (Bingley, U.K. : Emerald Publishing Limited, 2020)
Using an original empirical study of the frame building process in the press, this book analyses the interplay between political economy and framing theories, focusing on what the frames found in the press can reveal about structural power struggles, and the contribution of journalism to democratic debate.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Debts, Public -- Greece -- Press coverage; State bankruptcy -- Greece -- Press coverage; Business & Economics -- Economic Conditions; Economic & financial crises & disasters